280 A Case of Inflammatory Pseudotumor of the Liver Mimicking IgG4-Related Disease. (11th January 2018) - Zomorrodian, Sina; Yusuf, Yasmin; Saeed, Faisal
Abstract: Introduction: An inflammatory pseudotumor is a benign mass comprised of myofibroblasts and fibrous tissue with a marked inflammatory infiltrate composed of predominantly plasma cells. Immunoglobulin G4-related disease (IgG4-RD) is an increasingly recognized fibro-inflammatory condition that has been described in numerous organ systems. Generally, a confident diagnosis of IgG4-related disease requires the presence of two of three major histological features. These include a dense lymphoplasmacytic infiltrate, storiform-type fibrosis and obliterative phlebitis. Further supporting evidence includes elevated IgG4 levels, both in serum and histologically, as well as an IgG4+/IgG+ plasma cell ratio of greater than 40% on histology. Case Presentation: We report a case of a 46-year-old man initially presenting with elevated blood glucose levels and diabetic symptoms and subsequently found to have a 10 cm irregular hepatic mass on radiologic imaging. His total serum IgG levels were elevated; however, IgG4 levels were on the high end of normal range. Microscopic Description: Histology revealed diffuse areas of dense plasma-lymphocytic infiltrate and collagenized fibrosis. Plasma cells were mature, polyclonal and did not exhibit atypia. The infiltrate contained focal nonnecrotizing granulomas and giant cells, and neither storiform fibrosis nor obliterative phlebitis was noted. On immunohistochemistry IgG immunostain was strong and diffusely positive, and IgG4 varied in concentration from areas of more than 200 cells/hpf, to areas of 30–40 plasma cells/hpf. IgG4 to IgG ratio was estimated to be less than 20%. Discussion: The histological and immunohistochemical features support a diagnosis of a fibrohistiocytic type of inflammatory pseudotumor. However, given the dense lymphoplasmacytic infiltrate and elevated number of IgG4 plasma cells, an unusual variant of IgG4-RD is possible. Further studies of hepatic pseudotumors should be conducted in order to delineate sharper distinctions differentiating the two tumor types in the liver.